2021
DOI: 10.1038/s41598-021-92114-1
|View full text |Cite
|
Sign up to set email alerts
|

The composition of Australian Plantago seeds highlights their potential as nutritionally-rich functional food ingredients

Abstract: When wetted, Plantago seeds become covered with a polysaccharide-rich gel called mucilage that has value as a food additive and bulking dietary fibre. Industrially, the dry husk layer that becomes mucilage, called psyllium, is milled off Plantago ovata seeds, the only commercial-relevant Plantago species, while the residual inner seed tissues are either used for low value animal feed or discarded. We suggest that this practice is potentially wasting a highly nutritious resource and here describe the use of his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 99 publications
(96 reference statements)
1
16
0
Order By: Relevance
“…Arabinoxylan is a typical polysaccharide found in Plantago. Many reports describe its unusual branched structure β- (1,4) [142]. Plantago mucilage is a source of protein, dietary fiber, and saturated fatty acids.…”
Section: Plantagomentioning
confidence: 99%
See 1 more Smart Citation
“…Arabinoxylan is a typical polysaccharide found in Plantago. Many reports describe its unusual branched structure β- (1,4) [142]. Plantago mucilage is a source of protein, dietary fiber, and saturated fatty acids.…”
Section: Plantagomentioning
confidence: 99%
“…It is also a rich source of both ω-3 and ω-6 polyunsaturated acids (>78% of total fatty acids). The monosaccharides found in the hydrocolloid fractions include xylose, arabinose, rhamnose, galactose, glucose and small amounts of mannose, galactose, and galacturonic and glucuronic acids [142]. In the case of P. lanceolata, P. ovata, and P. media, additional cellulose fibrils form a regular, radially arranged skeleton of pectin, which surrounds the seed surface [143].…”
Section: Plantagomentioning
confidence: 99%
“…Colourimetric analysis presented here and used to determine the colour differences before and after rain damage showed that the rain event caused a significant darkening (reduction in L *) and a significant greening (reduction in a *) of the seeds (Figure 3a and b). The changes in seed colour determined using colourimetry likely reflect changes in the extractability and/or oxidation of pigments in the seeds which may be concentrated in an intensely stained layer between the mucilage polysaccharide layer and the endosperm tissues in P. ovata (Phan et al, 2020) and other Plantago species (Cowley et al, 2021; Jones & Albers, 1955; Patel et al, 2020; Qadry, 1963). Another possible explanation for the significant colour change in AR samples is microbial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…However, when looking in- depth at close relatives, there is often much variation (Figure 2D-E). Comparisons of many Plantago species reveal a wide variety of mucilage structure across the genus (Cowley & Burton, 2021, Cowley et al 2021) as does examining variation across populations of other widespread species or genera (e.g. Inceer et al, 2012; Villellas & Garcia, 2012, Poulain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%